Impact of disease-modifying therapies on evolving tissue damage in iron rim multiple sclerosis lesions: short report - Eisele, Philipp; Wittayer, Matthias Sebastian; Weber, Claudia Ellen; Platten, Michael; Schirmer, Lucas; Gass, Achim (Multiple sclerosis journal, 2022)
We investigated the impact of disease-modifying therapies (DMTs) on the evolving tissue damage in iron rim multiple sclerosis lesions using a novel post-processing magnetic resonance imaging (MRI) approach, the T1/T2 ratio. In this study, on baseline and 1-year follow-up, T1/T2 ratios of iron rim lesions (IRLs) in patients starting DMT (dimethyl fumarate, fingolimod, ocrelizumab) did not statistically differ compared to patients without DMT. At the second follow-up, T1/T2 ratios were significantly lower in IRLs in patients without DMT (p = 0.002), suggesting that DMTs have a beneficial delayed effect on lesion evolution and tissue matrix damage in IRLs.
Online veröffentlicht: 1. Juli 2022
Gesehen am 30.05.2023